A multi-method analysis of the interaction between humic acids and heavy metal ions. Issue 8 (3rd July 2018) - Ke, Tao; Li, Lu; Rajavel, Krishnamoorthy; Wang, Zhenyu; Lin, Daohui
ABSTRACT: Understanding of the interaction between humic acids (HAs) and heavy metal ions (HMIs) is essential for the assessment of environmental and health risks of HMIs. Multiple analyses, including fluorescence quenching of HAs; solution pH, zeta potential, and hydrodynamic size changes; and coprecipitation of HAs and HMIs, were carried out to investigate the interaction between two HAs and four HMIs (Ag +, Pb 2+, Cd 2+, and Cr 3+ ). The HA-HMI interaction mainly included chemical complexation, H + -HMI exchange, electrostatic attraction, and flocculation. The chemical complexation between HAs and HMIs revealed by the Stern–Volmer quenching constant was ordered as Ag < Cd < Pb < Cr. HMIs replaced protons in the acidic functional groups of HAs and thus lowered the pH of the solution. The electrostatic interaction between the negatively charged HAs and HMIs reduced the electronegativity of HAs. Interaction with HMIs, especially the high-valent ions, induced aggregation of HAs, causing precipitation of both HAs and HMIs in the sorptive solution. Cr 3+ flocculated and precipitated HAs, but at high concentrations, it reversed the surface charge of HAs and resuspended them. The HA-HMI interaction increased as the HA acidity and solution pH increased.